2012
DOI: 10.1179/1743281211y.0000000093
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on solid state recovery of metallic resources from EAF dust

Abstract: A new process to recover iron and zinc from electric arc furnace (EAF) dust in a solid state has been developed. It comprises three steps: (1) reduction of dust (,1000uC) using gas reductant with high H 2 or CO content; (2) for the solid product of step (1), wet magnetic separation to separate Fe from gangue; and (3) for the condensed fumes collected in step (1), water washing to remove soluble compounds like KCl and enrich and recover the zinc oxide. The performance of this process indicates that four kinds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Therefore the removal of zinc oxide from the dust makes it possible to recycle in stainless steel mill. In recent decades, some methods have been developed to process ZnO-bearing dust [1][2][3][4][5]. The methods can be classified into three groups: physical method, wet process (acid process and alkaline process), pyrogenic process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the removal of zinc oxide from the dust makes it possible to recycle in stainless steel mill. In recent decades, some methods have been developed to process ZnO-bearing dust [1][2][3][4][5]. The methods can be classified into three groups: physical method, wet process (acid process and alkaline process), pyrogenic process.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research on metallurgical dusts indicated that, [34] when the particle size is less than 0.01 mm, the reaction kinetic condition between particles and reducing gas in the fixed bed is poor, and the diffusion of the gas passing through the bed void takes a long time (2 hours) for ultrafine particles reduction. In order to improve the kinetic conditions of the gas-solid reaction, the contact area of reducing gas and particles should be increased, so use of fluidization has been considered.…”
Section: B Experimental Proceduresmentioning
confidence: 99%
“…High temperatures and long reaction times required for carbothermal reduction of zinc ferrite have raised the interests in investigation of gaseous reduction techniques for processing EAFD. Several researchers have suggested application of gaseous reducing agents for treatment of EAF dusts [10][11][12][13]16]. In this work, the isothermal reduction of zinc ferrite by hydrogen gas was examined.…”
Section: Gaseous Reduction Of Zinc Ferrite By Hmentioning
confidence: 99%
“…The Waelz kiln process is widely used for recycling of EAF dust. However, new reduction processes have been examined and proved to be effective in treatment of EAFD and obtaining products with lower impurities than the Waelz kiln process [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%